2021
DOI: 10.1158/0008-5472.can-20-3121
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Induces Adipocyte Dedifferentiation to Modulate the Tumor Microenvironment

Abstract: The most frequent location of metastatic EBV+ nasopharyngeal carcinoma (NPC) is the bone marrow, an adipocyte-dominant region. Several EBV-associated lymphoepithelioma-like carcinoma (LELC) types also grow in the anatomical vicinity of fat tissues. Here we show that in an adipose tissue-rich tumor setting, EBV targets adipocytes and remodels the tumor microenvironment. Positive immunoreactivity for EBV-encoded early antigen D was detected in adipose tissue near tumor beds of bone marrow metastatic NPC. EBV was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The titers of serum EBV antibodies are known to increase dramatically in NPC patients ( Chen et al, 2015 ). Interestingly, EBV has also been shown to be able to infect primary human adipocytes in vitro , leading to increased release of free fatty acids, glycerol, and expression of proinflammatory adipokines ( Liu et al, 2021 ). Further, EBV-encoded latent membrane protein 1 and EBV-encoded RNAs were shown to promote cell proliferation by upregulating fatty acid synthase in NPC cells ( Lo et al, 2018 ) whereas EBV-encoded latent membrane protein 2A (LMP2A) were shown to promote lipid accumulation by blocking adipose triglyceride lipase in NPC cells, resulting in an enhanced cell migration ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The titers of serum EBV antibodies are known to increase dramatically in NPC patients ( Chen et al, 2015 ). Interestingly, EBV has also been shown to be able to infect primary human adipocytes in vitro , leading to increased release of free fatty acids, glycerol, and expression of proinflammatory adipokines ( Liu et al, 2021 ). Further, EBV-encoded latent membrane protein 1 and EBV-encoded RNAs were shown to promote cell proliferation by upregulating fatty acid synthase in NPC cells ( Lo et al, 2018 ) whereas EBV-encoded latent membrane protein 2A (LMP2A) were shown to promote lipid accumulation by blocking adipose triglyceride lipase in NPC cells, resulting in an enhanced cell migration ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although they do not seem to affect the migration or invasion of cancer cells, EBV-encoded RNAs might confer a low-density lipoprotein-dependent proliferation in NPC cells ( Daker et al, 2013 ). Furthermore, EBV could target adipocytes to build a cancer-promoting environment by rewiring lipid metabolism, leading to increased levels of free fatty acids, glycerol, and proinflammatory cytokines ( Liu et al, 2021 ). Indeed, increased serum levels of free fatty acids have been shown to indicate a poor prognosis in NPC patients ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to oncolytic virus therapy has also been shown to be a lipid-dependent phenomenon ( Surendran et al, 2023 ). It has been suggested that EBV infection modulates gene expression in adipocytes, leading to dysregulation of their functionality and consequent changes in the tumour microenvironment ( Liu et al, 2021 ).…”
Section: Sars-cov-2 Infection As a Potential Risk Factor For The Deve...mentioning
confidence: 99%
“…In oncology, delving deeper into the nuanced and complex mechanisms orchestrated by viruses such as HPV and EBV within the TME is critical in fostering the evolution of potent therapeutic strategies. These viruses function as powerful catalysts, instigating a myriad of alterations within the TME, thereby influencing the pathogenesis and progression of associated malignancies [20,21]. Thus, it is paramount to unravel the intricate interplay between these viral entities and the TME to facilitate the development of targeted and effective therapies.…”
Section: Introductionmentioning
confidence: 99%